PENGARUH KEWAJARAN HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA APLIKASI GO-FOOD - Dewi, Luh Sukma Merta (Jurnal MBE Manajemen Bisnis, Equilibrium, 2024)
This research intends to determine the simultaneous and partial effect of price fairness and service quality on user satisfaction of the Go-Food application (a research problem for students of the Faculty of Economics and Business, Ngurah Rai University, Denpasar). Illustration dimensions were defined as the intentional collection method of illustrations from 72 people. Information analysis uses classical research, multiple linear regression analysis, deterministic analysis, F-test statistical analysis, and t-test statistical analysis. The findings confirm that the equality of price and service quality has a direct and clear impact on Go-Food user satisfaction as a simultaneous and local approach. Fairness of price and quality of service greatly affect the satisfaction of Go-Food application users.